BP's pipeline spills at Prudhoe Bay : what went wrong? : hearing before the Subcommittee on Oversight and Investigations of the Committee on Energy and Commerce, House of Representatives, One Hundred Ninth Congress, second session, September 7, 2006. - United States. Congress. House. Committee on Energy and Commerce. Subcommittee on Oversight and Investigations. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., U.S. G.P.O., 2006)
"Serial no. 109-135." Distributed to some depository libraries in microfiche. Shipping list no.: 2007-0114-M. Shipping list no.: 2007-0166-P. Includes bibliographical references. Mode of access: Internet.